The Geopolitical Problems of Eritrea (Journal of the College of Education for Women, 2019)
The subject of multi- ethnics is one of the most important subjects in the study of politicalgeography, as multi- ethnics and its consequent problems are global geopolitical phenomenathat started early and reached its peak with the beginning of the twentieth century, because ofmajor changes in the political landscape that resulted by wars and led to the collapse of manyempires and major powers, a matter which led to put new political maps according to certainconsiderations of the colonial powers, especially in Africa and Asia. All these things led tothe most serious challenges based on ethnic and sectarian conflict and led to the developmentof geopolitical problems. Among the examples what most countries in the Horn of Africahave suffered from, especially Eritrea, which is considered as a good example for countriesthat suffers from multi-ethnic problems.Among the most important ethnic groups that are related to the problems of Eritrea are theAfar, Beja, and Altgerin. These three geopolitical ethnics make many problems to Eritrea andneighboring countries. What increases the seriousness of this situation is the geographicaldistribution of these ethnic groups in Eritrea and neighboring countries as shown in map 1.The presence of Afar, Beja and Altgerin in neighboring countries is a problem that hasgeopolitical dimensions that affects in the national security of Eritrea as Al- Afar occupiesabout 9.5% of the area of the neighboring country of Ethiopia, as well as most land inDjibouti is inhabited by Alafrien. Such situation increases the danger on security of Eritreaespecially the existence of these ethnics lies in the most important geo-strategic dimension, asthey live in Massawa that lies on The Red Sea and along the coast till the Dahlak Islands,which makes it among the most important geopolitical challenges to Eritrea. This danger isnot related only to the Afar, but it includes other ethnicities such as the Beja and Altgerinwhich extend on the borders of Eritrea and the neighboring countries, and threaten thesecurity of Eritrea, especially from its neighbor Ethiopia.